Sustainable Development of Tay Ethnic Village Spaces in Tuyen Quang Province Through The Preservation and Utilization of Traditional Architectural Values - Nguyen, Dinh Thi; Vu, Thi Huong Lan; Le, Nam Phong; Pham, Thi Hong Tho; Nguyen, Hoai Thu (International Journal of Sustainable Construction Engineering and Technology, 2025)
This study investigates the sustainable development of Tay ethnic village spaces in Tuyen Quang province, Vietnam, through the preservation and use of traditional architectural values. Indigenous architectural techniques - formed over many generations to adapt to natural, cultural and social conditions - are rapidly being lost due to urbanization, livelihood transformation and changing development pressures. The study used a multi-method approach, including literature review, field survey, expert consultation and community interviews, with a methodology emphasizing “community-based planning” to assess the current status of traditional architecture and community needs. Focusing on Tan Lap village in Tan Trao commune, the study identified the main architectural features, spatial configurations and socio-cultural functions of Tay stilt houses. Based on these findings, the study proposes sustainable spatial planning strategies that integrate traditional values ??with contemporary needs to support cultural preservation, community-based tourism and sustainable rural development. This study contributes to ongoing efforts to protect ethnic heritage while promoting inclusive and adaptive rural planning.